The Effect of SIRT3/Ac-SOD2 Mediated Oxidative Stress and HCN1 Channel Activity on Anesthesia/Surgery Induced Anxiety-Like Behavior in Mice - Miao, Hui-Hui; Liu, Qiang; Wang, Ning; Liu, Yan-Ping; Chen, Chen; Wang, Hai-Bi; Huang, Hui; Wu, Wei-Feng; Lin, Jia-Tao; Qiu, Yong-Kang; Zhang, Chuan-Wu; Zhou, Cheng-Hua; et al. (Frontiers in Medicine, 2022)
Anxiety disorders represent the most common psychiatric diseases and perioperative related factors often increase the incidence of anxiety. However, the mechanism and treatment for perioperative anxiety especially anesthesia/surgery-induced postoperative anxiety is still largely unknown. Sirtuin 3 (SIRT3) which located in the mitochondria is the NAD-dependent deacetylase protein. SIRT3 mediated oxidative stress is associated with several neuropsychiatric diseases. In addition, hyperpolarization-activated cyclic nucleotide-gated 1 (HCN1) channel is also reported involved in anxiety symptoms. The purpose was to assess the role of SIRT3 on postoperative anxiety like behavior in C57/BL6 mice. We found that SIRT3 level reduced and HCN1 expression level increased in mice medial prefrontal cortex (mPFC) as well as anxiety like behavior postoperatively. In the interventional research, the SIRT3 adeno-associated virus (AAV) vector or control vector was injected into the mPFC brain region. Enzyme-linked immune-sorbent assay (ELISA), immunofluorescence staining and western blotting were emplored to detect oxidative stress reaction and HCN1 channel activity. As result, overexpress SIRT3 attenuated postoperative anxiety disorder. Superoxide dismutase 2 (SOD2) acetylation level, oxidative stress of SOD2 activity and mitochondrial membrane potential (MMP) level and HCN1 channel were also inhibited by SIRT3 overexpression accordingly. Furthermore, HCN1 channel inhibitor ZD7288 significantly protected anesthesia/surgery induced anxiety but without SIRT3/ac-SOD2 expression nor oxidative stress changed. Our results suggest that SIRT3 may achieve anti-anxiety effect through regulation of SOD2 acetylation mediated oxidative stress as well as HCN1 channel in mPFC, further strengthening the therapeutic potential of targeting SIRT3 for anesthesia/surgery induced anxiety-like behavior.